Case Report: A 55 kg retroperitoneal liposarcoma - Yingzheng, Ren; Junjie, An; Guifei, Wang; Yang, Yang; Long, Dong; Linlin, Jiang; Zhiqiang, Fang; Xiaogang, Bi; Yonghong, Dong (Frontiers in Oncology, 2025)
BackgroundSarcomas, which are mesenchymal malignancies, account for less than 1% of all cancers. Retroperitoneal liposarcoma (RPLS), particularly the well-differentiated subtype, often presents as large masses due to its deep anatomical location and indolent growth pattern. Moreover, its frequent adherence to vital structures poses significant challenges for complete surgical resection.Case presentationA 62-year-old male was admitted to the hospital due to the gradual enlargement of a mass in the abdomen and pelvis over the past 20 years. In the recent five months, the mass has significantly increased in size, leading to compression symptoms such as dyspnea and lower limb edema. Physical examination showed that the abdomen was distended, and varicose veins on the abdominal wall were visible. The peak value of the abdominal circumference reached 165 cm. Abdominal and pelvic CT examination indicated that there was a huge mass with mixed density in the abdominal and pelvic cavity, which contained lipid, calcification, and soft tissue density shadows. The lesion was so huge that it exceeded the scanning field, and its size could not be measured. Subsequently, the patient underwent a resection of the huge retroperitoneal tumor and a combined resection of multiple organs under general anesthesia. The huge retroperitoneal mass, approximately 70*54*20 cm in size and weighing 55 kg, was removed. The postoperative pathology confirmed it as well-differentiated liposarcoma. The surgical process was relatively smooth. However, unfortunately, 40 days after the operation, the patient died of multiple organ dysfunction due to pneumonia, heart failure, and intra-abdominal infection after anastomotic leakage.ConclusionsWhile Complete surgical resection (R0) remains the gold standard for RPLS management, radical multivisceral resection of massive tumors requires meticulous evaluation by a multidisciplinary team (MDT), encompassing patient fitness, tumor biology, and perioperative risk stratification. When achieving R0 resection is deemed unfeasible or carries prohibitive risks, staged debulking surgery may be considered as an alternative approach. The application of hyperthermic intraperitoneal chemotherapy (HIPEC) should be evaluated judiciously on a case-by-case basis.